Indigenous Systems for a Sustainable Development: Some Issues in the Revitalization of Sikko-Mando Gadaa under Oda Roba, South-Eastern Ethiopia: Research article - Tessema Semu, Kefyalew (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2023)
This article explores the revitalization of the Sikko-Mando Gadaa system by analyz-ing historical sources and addressing the challenges faced in renewing the values of the system. The study highlights the system's ability to blend past traditions with new socioeconomic realities, demonstrating both continuity and adaptability. In response to socioeconomic and political changes, modifications were made to the Sikko-Mando Gadaa system, including the decentralization of power to operate more ef-fectively at the clan level while maintaining a strong connection to the central Caffee at Oda Roba. This involved a rule of five gadaa classes sharing authority on an eight-year rotational basis, a practice that was suspended over a century ago. Recent re-search has recommended indigenous systems, like the Oromo Gadaa System, as a means to address societal challenges and promote sustainable development. The ef-forts to reinstate the Oromo Gadaa System have gained momentum, supported by its recognition as an intangible heritage of humanity by UNESCO. The Sikko-Mando Gadaa has been undergoing a revival under Oda Roba, with representatives from the Arsi Oromo community since May 2018. However, the revitalization process has faced divergent views within the Arsi Hayyuu community. Therefore, adjustments need to be made considering the specificities, heera and seera, sub-centers, power structure, agnatic and geographic organizations of the Sikko-Mando Gadaa system, aligning them with the existing realities of the Arsi people and the principles of Oromo Gadaa philosophy.